Matrix metalloproteinases -8 and -9 in the Airways, Blood and Urine During Exacerbations of COPD. (2nd January 2016) - Cane, Jennifer L.; Mallia-Millanes, Brendan; Forrester, Douglas L.; Knox, Alan J.; Bolton, Charlotte E.; Johnson, Simon R.
Abstract: Matrix metalloproteinases (MMPs) are elevated in the airways and blood of COPD patients, contributing to disease pathogenesis and tissue remodelling. However, it is not clear if MMP levels in airways, blood and urine are related or if MMP levels are related to disease severity or presence of exacerbations requiring hospitalisation. Seventy-two patients requiring hospitalisation for COPD exacerbations had serum, urine and sputum MMP-8, -9 and active MMP-9 measured by ELISA and gelatin zymography on day one, five and four weeks later (recovery). Clinical history, spirometry, COPD Assessment Test and MRC dyspnoea score were obtained. Twenty-two stable COPD patients had MMP measurements one week apart. During exacerbations, serum and urine MMP-9 were slightly elevated by 17% and 30% compared with recovery values respectively (p = 0.001 and p = 0.026). MMP-8 was not significantly changed. These MMP levels related to serum neutrophil numbers but not to outcome of exacerbations, disease severity measures or smoking status. In clinically stable patients, serum MMP levels did not vary significantly over 7 days, whereas urine MMPs varied by up to nine fold for MMP-8 (p = 0.003). Sputum, serum and urine contained different MMP species and complexes. Median values for sputum active MMP-9 were significantly different from serum (p = 0.035) and urine (p = 0.024). Serum and urine MMPs are only modestly elevated during exacerbations of COPD and unlikely to be useful biomarkers in this clinical setting. Airway, serum and urine MMP levels are independent of each other in COPD patients. Further, MMP levels are variable between patients and do not reflect airflow obstruction.